Monologue and silence in the teachers’ meetings: The subjective positions that education policy places on managers and teachers in two non-selective public schools in Chile - Acuña, Felipe; Contreras, Paulina; Assaél, Jenny (Education Policy Analysis Archives, 2019)
The traditional approach of the cycle of an education policy follows a clear direction: from up and outside (design and evaluation), to down and inside (implementation). The school has in this approach the position of implementation. However, it is possible to think that, according to its own necessities and possibilities, a process of creative translation (re-contextualisation) of the diverse educational policies that circulate in a particular school takes place. The teachers’ meeting, the formal place where the professionals of a school meet, is a privilege space to study this process of policy re-contextualisation. Based on six years (2012-2018) of ethnographic work in three non-selective public school in Chile, this paper analyses the intense work done in two of these schools during the years 2012 – 2014. The main purpose is to shed light on the definitive closure experienced by one of these schools at the end of 2016. Considering the perceptions that teachers and managers had about the teachers’ meetings as a boring and tedious space, we elaborates on two subjective positions, the managers’ monologue and teachers’ silence. Both positions give an account of the way in which education policy is enacted, a way characterised by a subjective split that hinders the possibilities of a reflective dialogue.